Gastric Perivascular Epithelioid Cell Tumor (PEComa): A Morphologic, Immunohistochemical, and Molecular Study. Issue 2 (29th May 2019) - Xu, Jinghong; Yan, Yu; Xiang, Xueping; Jiang, Peter; Hu, Xiangrong; Yang, Wenjun
Abstract: Objectives: To review the clinicopathologic, immunophenotypic, and molecular features of gastric perivascular epithelioid cell tumor (PEComa). Methods: We identified two new cases of gastric PEComa and summarized the clinical and pathologic characteristics of this rare neoplasm. Results: The first case was a 48-year-old woman who was treated with an endoscopic submucosal dissection (ESD), and the second case was a 64-year-old man who received a distal gastrectomy. Microscopic examination showed one tumor was composed of purely epithelioid cells, while the other was composed of epithelioid and spindle cells. Both tumors were immunoreactive for melanocytic markers (HMB45 and Melan-A), smooth muscle actin, and vimentin. No TFE3 gene rearrangement was identified by fluorescence in situ hybridization in either case. Conclusions: Gastric PEComa is an exceedingly rare neoplasm, with only seven other reported cases to date. We are the first to report the results of molecular assays for the TFE3 gene rearrangement associated with gastric PEComa.